Sketch Learning by Using Demonstration Method for Early Semester Students - Muslim Muslim (BIRCU, 2022)
This study is purposed to describe sketch learning by using demonstration method for early semester students in which the sketch learning by using demonstration method is a good way to develop the creativity of early students because not all of them have the ability to make sketches. This study used a CAR (Classroom Action Research) research method in which 36 art students were the subjects of this study. The study results explained that in cycle I of CAR, the ability of the students in sketch learning was still low because out of 36 students, there were 25 students (69.4%) who received a pretty good predicate and 11 students (30.6%) who got a good predicate, so it needs the cycle II of CAR. In the cycle II of CAR, the results obtained were very satisfying where out of 36 students there were 7 students (19.4%) who received a pretty good predicate, 28 students (77.8%) who got a good predicate and only 1 student (2.8 %) got a very good predicate. Therefore, learning sketches using the demonstration method is a good way to apply to early semester students in developing the students' skills in learning sketches.